Emodepside: the anthelmintic’s mode of action and toxicity - Njeshi, Charity N.; Robertson, Alan P.; Martin, Richard J. (Frontiers in Parasitology, 2024)
Nematode parasitic infections continue to be a major health problem for humans and animals. Drug resistance to currently available treatments only worsen the problem. Drug discovery is expensive and time-consuming, making drug repurposing an enticing option. Emodepside, a broad-spectrum anthelmintic, has shown efficacy in the treatment of nematode parasitic infections in cats and dogs. It is now being considered and trialed for the treatment of onchocerciasis, trichuriasis (whipworm), and hookworm infections in humans. Its unique mechanism of action distinguishes it from traditional anthelmintics, positioning it as a promising candidate for combating resistance to other current drugs. Here, we provide a brief review of the available information on emodepside’s pharmacokinetics, safety, and tolerability. We highlight the potential benefits and risks associated with its use, examining key toxicity effects. By exploring the literature, we aim to provide insights into the risks associated with emodepside that may impact its application in veterinary and human medicine. Although emodepside demonstrates a favorable safety profile, continued monitoring of its toxicity is crucial, particularly in vulnerable populations. This mini-review serves as a concise resource for researchers and clinicians interested in anthelmintic therapy.